STUDY ON EFL CLASSROOM MANAGEMENT IN CLASSROOM AT SMP NEGERI 13 AMBON - Yulia Sarah (JURNAL TAHURI, 2022)
Inclusive classroom is widely discussing around the countries regarding the benefits and the challenges of EFL teachers’ constraints in managing the inclusive classroom. This study is aimed at finding out (1) the facts of inclusive classroom management in EFL teaching and learning process, (2) the challenges faced EFL teachers in managing the inclusive classroom and (3) the new insights proposed by EFL teachers for better improvement in managing the inclusive classroom. The findings of the study revealed that; a) Both EFL teachers have clear comprehension about the concepts of classroom management for inclusive classroom but they realized that they didn’t optimally implemented the principles of inclusive classroom management. The challenges faced by the EFL teachers in managing inclusive classroom are; a) lack of competencies, b) lack of trainings, c) limitation of teaching and learning facilities based on inclusive students’ needs, d) Lack of concrete teaching materials, e) large classes, and f) time allocation. The new insights proposed by EFL teachers can be recommendations for better improvement in managing inclusive classroom in the future